2018
DOI: 10.1080/15384047.2018.1423919
|View full text |Cite
|
Sign up to set email alerts
|

PD1 protein expression in tumor infiltrated lymphocytes rather than PDL1 in tumor cells predicts survival in triple-negative breast cancer

Abstract: To determine PD1/PDL1 expression status in triple-negative breast cancer (TNBC) at both protein and mRNA levels, and to analyze the relationship between their expression and clinical parameters of the TNBC patients. Immunohistochemistry and RNAscope were used to semi quantitively evaluate PD1/PDL1 protein and mRNA expression in 195 TNBC cases on tissue microarrays. Tumor infiltrating lymphocyte (TILs) abundance was assessed using hematoxylin-eosin staining. Both tumor cells and TILs expressed PDL1. PDL1 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 41 publications
9
52
1
Order By: Relevance
“…We have previously shown that PD‐L1 gene expression is associated with prolonged DFS and OS (Matikas et al , 2019b). In the present study, we confirm that PD‐L1 gene expression is correlated with improved outcomes, while we also demonstrate a significant correlation between PD‐L1 mRNA and protein expression, helping to clarify currently available inconsistent studies that have reported high (Guo et al , 2016; Kim et al , 2017), moderate, or low protein–mRNA correlation (Ali et al , 2015; Ren et al , 2018). PD‐L1 mRNA can thus be a promising and reliable prognostic marker compared with current IHC methods but with unclear—up until now—clinical validity and utility.…”
Section: Discussionsupporting
confidence: 84%
“…We have previously shown that PD‐L1 gene expression is associated with prolonged DFS and OS (Matikas et al , 2019b). In the present study, we confirm that PD‐L1 gene expression is correlated with improved outcomes, while we also demonstrate a significant correlation between PD‐L1 mRNA and protein expression, helping to clarify currently available inconsistent studies that have reported high (Guo et al , 2016; Kim et al , 2017), moderate, or low protein–mRNA correlation (Ali et al , 2015; Ren et al , 2018). PD‐L1 mRNA can thus be a promising and reliable prognostic marker compared with current IHC methods but with unclear—up until now—clinical validity and utility.…”
Section: Discussionsupporting
confidence: 84%
“…[1] When evaluated in 136 cases of IDC (NST) in the current study, we found positive expression of PDL1 in 58.8% of cases. Our figure for PDL1 was concor-dant to that reported by Baptista et al (2016), higher than Muenst et al (2014) who reported 23.4%, and much higher than Ren et al (2018) who found it to be 6.7%. [12][13][14] On the other hand, Beckers et al (2016) reported a much higher percentage (64%) but their study included only triple-negative breast cancer cases that may explain this high difference with ours.…”
Section: Discussionsupporting
confidence: 70%
“…Our figure for PDL1 was concor-dant to that reported by Baptista et al (2016), higher than Muenst et al (2014) who reported 23.4%, and much higher than Ren et al (2018) who found it to be 6.7%. [12][13][14] On the other hand, Beckers et al (2016) reported a much higher percentage (64%) but their study included only triple-negative breast cancer cases that may explain this high difference with ours. [15] Considering the prognostic role of PDL1, we found a significant correlation of PD L1 with two poor prognostic parameters which are high proliferative index and advanced stage.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A cut‐off of ≥1 was considered to be statistically significant. Low expression was defined as a score of 0, and high expression was defined as a score of ≥1 …”
Section: Methodsmentioning
confidence: 99%